2017
DOI: 10.1186/s12950-017-0164-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-35 on B cell and T cell induction and regulation

Abstract: Interleukin (IL)-35 is a relatively newly discovered member of IL-12 cytokine family that is unique in that it is a dimer formed by two subunits. The review documents the structure, secretion and signal transduction of IL-35, the regulation effect of IL-35 on B cells and T cells as well as the adoptive transfer of IL-35+ regulatory B cells (Breg), therapeutic prospects of recombinant IL-35 (rIL-35) and IL-35 regulation role in various diseases. B-cell regulation expands the regulatory range of IL-35 and alters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…IL‐35 is identified as an anti‐inflammatory and immunosuppressive cytokine which is mainly produced by Treg cells . The results of the present study showed that the serum IL‐35 levels in PU patients were significantly decreased compared with AS and NHS groups.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…IL‐35 is identified as an anti‐inflammatory and immunosuppressive cytokine which is mainly produced by Treg cells . The results of the present study showed that the serum IL‐35 levels in PU patients were significantly decreased compared with AS and NHS groups.…”
Section: Discussionmentioning
confidence: 47%
“…IL‐35 has been described as a novel cytokine with anti‐inflammatory and immunomodulatory properties, constituted by the IL‐12p35 and Epstein‐Barr virus‐induced gene 3 (EBI3) subunits . It is produced by Treg cells and a particular CD4 + Treg cells subgroup, called IL‐35‐induced CD4 + Treg (iTr35) cells, because their proliferation is promoted precisely by IL‐35 . The IL‐35 receptor is composed of IL‐12Rβ2 and gp130, which are also associated with the IL‐12 and IL‐27 receptors, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These properties make MSC as a promising potential treatment of autoimmune diseases. 1 Our previous studies have found that bone marrow-derived (BM)-MSC from systemic lupus erythematosus (SLE) patients are defective structurally and functionally, 2 treatment with modified and optimised MSC may bring a better effect on patients with autoimmune diseases. Most efforts have relied on adeno-and lentiviral vectors for delivering genes to MSC.…”
mentioning
confidence: 99%